Credit Management Practices, Loan Repayment Management and Profitability Of Commercial Banks’ Branches In Uganda. - Elemu, Anthony (Student’s Journal of Health Research Africa, 2021)
Background: The study examined the relationship between credit management practices, loan repayment management, and profitability of commercial banks branches in Uganda. The objectives included; establishing the relationship between credit management practices and profitability; the relationship between loan repayment management and profitability; mediating the effect of loan repayment management on credit management practices and profitability, and examining the impact of credit management practices and loan repayment management on profitability. Methodology: The study was cross-sectional research and applied a quantitative approach. A sample of 234 commercial bank branches was used from a total of 573. The study obtained responses from 166 branches. Primary data was obtained from a branch manager and credit supervisor using a structured questionnaire. Validity of the questionnaire was obtained using CVI and reliability using Cronbach Alpha Coefficient. Data were analyzed using SPSS v.20 to obtain descriptive statistics, correlation, and regression analyses to present results. A Med-graph was used to test the mediation of loan repayment management. Results: This study ascertained a positive relationship between credit management practices and profitability; and a positive relationship between loan repayment management and profitability. The study further ascertained a partial mediation of loan repayment management in the relationship between credit management practices and profitability. Furthermore, the study revealed that jointly credit management practices and loan repayment management predict the profitability of commercial bank branches. This study ascertained a positive relationship between credit management practices and profitability; and a positive relationship between loan repayment management and profitability. Conclusion: The study concludes that credit management practices and loan repayment management are among the critical factors influencing profitability at the commercial bank branch level. Recommendations: The study recommends commercial bank branches carry out continuous loan monitoring and control; loan appraisal; and proper documentation.